Biological market effects predict cleaner fish strategic sophistication. (29th June 2019) - Triki, Zegni; Wismer, Sharon; Rey, Olivia; Ann Binning, Sandra; Levorato, Elena; Bshary, Redouan
Abstract: Market-like situations emerge in nature when trading partners exchange goods and services. However, how partner choice option contributes to the expression of social strategic sophistication (i.e., the ability to adjust behavior flexibly given the specifics of a situation) is still poorly understood. A suitable study system to explore this question is the "cleaner" fish Labroides dimidiatus . Cleaners trade parasite removal in exchange for food with a variety of "client" species. Previous research documented strong interindividual variation in two features of their strategic sophistication, namely, the ability to adjust service quality to the presence of an audience and to give priority to clients with access to alternative cleaners ("visitor clients") over clients lacking such choice options ("resident clients"). Here, we sampled various demes (i.e., group of individuals) of the same population of cleaner fish in order to investigate the extent to which factors describing fish densities and cleaning interaction patterns predict the strategic sophistication in two laboratory experiments. These experiments tested whether cleaners could increase their food intake through reputation management and/or learning to provide service priority to a visitor-like ephemeral food plate. We found that high "outbidding competition, " characterized by high densities of cleaners and visitor clients, along with visitor's behavior promoting such competition, consistently predicted high strategic sophistication in cleaners. A better understanding of the role of learning versus potential genetic factors, interacting with local market conditions to affect strategic sophistication, is needed to clarify how natural selection has promoted the evolution and maintenance of cooperation in this cleaning mutualism. Abstract : Market-like situations emerge when trading partners exchange goods and services in nature. Using a marine cleaning mutualism as a study model, we show that market effects can shape individual behavioral strategies. The abundance of the traders and the option of applying partner choice were the main drivers of the complexity of the behavioral strategies applied by the individuals.